2021
DOI: 10.1186/s13567-021-00979-x
|View full text |Cite
|
Sign up to set email alerts
|

Mutual regulation between chicken telomerase reverse transcriptase and the Wnt/β-catenin signalling pathway inhibits apoptosis and promotes the replication of ALV-J in LMH cells

Abstract: This study aimed to explore the mutual regulation between chicken telomerase reverse transcriptase (chTERT) and the Wnt/β-catenin signalling pathway and its effects on cell growth and avian leukosis virus subgroup J (ALV-J) replication in LMH cells. First, LMH cells stably overexpressing the chTERT gene (LMH-chTERT cells) and corresponding control cells (LMH-NC cells) were successfully constructed with a lentiviral vector expression system. The results showed that chTERT upregulated the expression of β-catenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Avian leghorn male hepatoma ( LMH ) cell line stably overexpressing the chTERT (HA-tag) gene (LMH-chTERT) and control cells (LMH-NC) were constructed by our laboratory in previous study ( Xiang et al, 2021 ). The cells were cultured in DMEM/F12 (Gibco, Thermo Fisher Scientific, Inc.) supplemented with 10% fetal bovine serum and maintained at 37°C and 5% CO 2 .…”
Section: Materials and Mtehodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Avian leghorn male hepatoma ( LMH ) cell line stably overexpressing the chTERT (HA-tag) gene (LMH-chTERT) and control cells (LMH-NC) were constructed by our laboratory in previous study ( Xiang et al, 2021 ). The cells were cultured in DMEM/F12 (Gibco, Thermo Fisher Scientific, Inc.) supplemented with 10% fetal bovine serum and maintained at 37°C and 5% CO 2 .…”
Section: Materials and Mtehodsmentioning
confidence: 99%
“…LMH cells are an avian-derived tumor cell line, which can be used as an in vitro research model for tumor diseases such as avian leukosis and Marek's disease. Our previous research results showed that overexpression of chTERT can up-regulate the Wnt/β-catenin signaling pathway to shorten the LMH cell cycle, inhibit cell apoptosis, promote cell proliferation and the replication of avian leukosis virus subgroup J ( ALV-J ); conversely, the expression of chTERT can also be upregulated after infected ALV-J ( Xiang et al, 2021 ). This study showed that overexpression of chTERT can promote pyroptosis by up-regulating the NF-κB signaling pathway in LMH cells.…”
Section: Disscussionmentioning
confidence: 99%
“…The results showed that the methylation level of the chTERT promoter region in LMH cells was higher than that in DF-1 cells (Figure 2). Our previous study showed that telomerase activity was positive in LMH cells and negative in DF-1 cells [33]; that is, chTERT was not expressed in DF-1 cells. In conclusion, the expression of chTERT in LMH cells is related to the hypermethylation level of the promoter region.…”
Section: Resultsmentioning
confidence: 92%
“…Expression levels were quantified using the 2 −ΔΔCt method and normalized to GAPDH expression. The sequences of the primers used were the same as those used in our previous study [33].…”
Section: Real-time Fluorescence Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…The chicken telomerase reverse transcriptase (chTERT) might play a regulatory role in the process. chTERT is mutually regulated with the Wnt/β-catenin signaling pathway to inhibit apoptosis, promote ALV-J replication, and increase telomerase activity ( 71 ). The activation of the ERK/MAPK pathway is required for ALV-J replication and is associated with virus-induced tumorigenesis ( 72 ).…”
Section: Cellular Factors Affecting Alv Replicationmentioning
confidence: 99%